Intercalation and controlled release properties of vitamin C intercalated layered double hydroxide - Gao, X; Lei, L; O'Hare, D; Xie, J; Gao, P; Chang, T (2013)
Two drug-inorganic composites involving vitamin C (VC) intercalated in Mg-Al and Mg-Fe layered double hydroxides (LDHs) have been synthesized by the calcination-rehydration (reconstruction) method. Powder X-ray diffraction (XRD), Fourier transform infrared (FTIR), and UV-vis absorption spectroscopy indicate a successful intercalation of VC into the interlayer galleries of the LDH host. Studies of VC release from the LDHs in deionised water and in aqueous CO 32- solutions imply that Mg3Al-VC LDH is a better controlled release system than Mg3Fe-VC LDH. Analysis of the release profiles using a number of kinetic models suggests a solution-dependent release mechanism, and a diffusion-controlled deintercalation mechanism in deionised water, but an ion exchange process in CO32- solution. © 2013 Elsevier Inc. All rights reserved.